2011
DOI: 10.1016/j.chembiol.2011.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Traffic Jam at the Bacterial Sec Translocase: Targeting the SecA Nanomotor by Small-Molecule Inhibitors

Abstract: The rapid rise of drug-resistant bacteria is one of the most serious unmet medical needs facing the world. Despite this increasing problem of antibiotic resistance, the number of different antibiotics available for the treatment of serious infections is dwindling. Therefore, there is an urgent need for new antibacterial drugs, preferably with novel modes of action to potentially avoid cross-resistance with existing antibacterial agents. In recent years, increasing attention has been paid to bacterial protein s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 145 publications
0
37
1
Order By: Relevance
“…6B). Even though it has been suggested that the lack of SecA or inhibition of SecA is bactericidal (35), these results suggest that depletion was bacteriostatic in LVS; however, at later time points, suppression of the secA deletion did occur in both strains, which obfuscates the results. As it was difficult to maintain a clean population of the TetOn strain because of constant selective pressure, the revTetR system would likely be a better system to use when studying a potentially essential gene.…”
contrasting
confidence: 51%
“…6B). Even though it has been suggested that the lack of SecA or inhibition of SecA is bactericidal (35), these results suggest that depletion was bacteriostatic in LVS; however, at later time points, suppression of the secA deletion did occur in both strains, which obfuscates the results. As it was difficult to maintain a clean population of the TetOn strain because of constant selective pressure, the revTetR system would likely be a better system to use when studying a potentially essential gene.…”
contrasting
confidence: 51%
“…For a detailed discussion, readers are referred to an extensive review written by Segers et al [91], which discusses in-depth information available on small-molecule SecA inhibitors. One special point that we would like to make is the possibility of SecA to be accessible by inhibitors from the periplasm (Gram-negative) or the extracellular matrix (Gram-positive).…”
Section: Reported Seca Inhibitorsmentioning
confidence: 99%
“…Such conformational changes of SecA in the membranes alter its sensitivities and the various ATPase activity of SecA in response to SecA inhibitors, sodium azide [20] and Rose Bengal [21]. Inhibitors for SecA and protein translocation have been the topics of extensive studies [reviews [22,23]. Azide has been found to be an effective inhibitor for SecA-dependent translocation, and the mutation of azide-resistant mutant resides in SecA [20].…”
Section: Introductionmentioning
confidence: 99%